PERAN KEPUASAN KERJA DAN DUKUNGAN ORGANISASI DALAM MEMEDIASI HUBUNGAN ANTARA EFIKASI DIRI DENGAN KINERJA KARYAWAN (Studi Kasus di Yayasan Pendidikan Ariyanti) - Wiyono, Darul (Universitas Prof. Dr. Hazairin SH, 2022)
This research aims to find out how big the role of job satisfaction and organizational supportin mediating the relationship between self-efficacy and employee performance at the AriyantiEducation Foundation. This research is a descriptive and verification research, the researchmethod used is explanatory survey, and data analysis using a structural equation modelStructural Equation Model, SEM) through the Partial Least Square (PLS) method processedwith the application of SmartPLS 3.3.7 statistics. The number of respondents was 63 obtainedthrough the distribution of questionnaires with the stratified proportional random samplingmethod. The results of the research explain that job satisfaction and organizational supportcan mediate well between self-efficacy and employee performance at the Ariyanti EducationFoundation by 62,70%. This study has limitations in terms of the conceptual framework used,namely only connecting variables that are estimated to have a relationship with thedependent variable so that there are still possibilities for other variables that have not beenincluded in the conceptual framework.